Does Dual Vocational Education and Training Pay Off? - Samuel Bentolila; Antonio Cabrales; Marcel Jansen (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper analyzes the causal impact of dual vocational education and training (VET) on the labor market insertion of youth. Using matched education and social security records, we estimate the causal impact of a major reform that introduced a new dual track, which combines firm- and school-based training, on the labor market outcomes of the first three dual VET cohorts in the Spanish region of Madrid. The control group is composed of individuals who graduated in the same fields and years in school-based VET. Selection into dual VET is dealt with using a distance-based instrumental variable. Dual VET is found to generate sizable improvements in employment and earnings, but no significant impact on job quality. The results are not driven by pre-reform differences in the quality of the schools that adopted dual VET and the higher retention rate of dual VET graduates only partly explains the dual premium.
Keywords: D92; G33; J23; 330; dual vocational education and training; school-to-work transition; Spain